2015
DOI: 10.5713/ajas.14.0535
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Changes in Enzyme and Insulin-like Growth Factor-1 Concentrations in Blood Serum and Growth Characteristics of Velvet Antler during the Antler Growth Period in Sika Deer (<i>Cervus nippon</i>)

Abstract: This study was conducted to investigate changes in blood enzyme parameters and to evaluate the relationship between insulin-like growth factor-1 (IGF-1), antler growth and body weight during the antler growth of sika deer (Cervus nippon). Serum enzyme activity and IGF-1 concentrations were measured in blood samples collected from the jugular and femoral veins at regular intervals during the antler growth period. Blood samples were taken in the morning from fasted stags (n = 12) which were healthy and showed no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Estimates of regression coefficients of age ( and 4.36) and field-dressed weight ( and 0.75) in Eq 1 showed that there were positive linear relationships between the effects of age and field-dressed weight and the traits of antler beam diameter and length. This result is consistent with previous reports [6, 7, 43]. Our results also showed that age is related to antler characteristics and body size in WTD.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Estimates of regression coefficients of age ( and 4.36) and field-dressed weight ( and 0.75) in Eq 1 showed that there were positive linear relationships between the effects of age and field-dressed weight and the traits of antler beam diameter and length. This result is consistent with previous reports [6, 7, 43]. Our results also showed that age is related to antler characteristics and body size in WTD.…”
Section: Resultssupporting
confidence: 94%
“…The relationships among antler characteristics, age and field-dressed weight and predictions of these traits in deer populations have been studied by using linear models [6, 7]. Significant literature exists related to the use of body measurement, such as antler size, to predict age, as well as correlation between antler size and body weight.…”
Section: Introductionmentioning
confidence: 99%
“…During velvet regeneration and development, plasma levels of IGF1 are significantly elevated during the velvet antler growth phase, relative to the other phases of pedicle, as well as first antler development, and a strong positive correlation exists between antler growth rate and circulating concentrations of IGF1 [ 8 ]. The effects of IGF1 on the growth of the fibroblast and cartilage zones were investigated; IGF1 was found to be mitogenic for cells originating from the perichondrium, mesenchyme, and cartilage zone of antler [ 9 , 10 ]. The localization of IGF1 in chondrocytes and osteoblasts also suggests that IGF1 may play an important role in cartilage and bone formation [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this fundamental pursuit, antler measurement is of considerable importance to other scientific investigations focused on determining the effects of systemic hormones and local growth factors (specifically insulin‐like growth factor) on antler growth (Park et al., ), determining the relationship between temperature and antler growth (Bowers et al., ), quantifying the variation of body mass and antler size with animal age and sex (Melnycky et al., ), and identifying the correlation between live weight and first antler development (Ward et al., ). Antler measurement also has several very practical applications with significant economic impact including the identification of sires for breeding (Ward et al., ) and the determination of optimal velvet harvest time (Bowers et al., ).…”
Section: Introductionmentioning
confidence: 99%